(untitled) - Ministry of Finance Department of Accounting Policy (Hà Nội, 1996)
Vietnamese accounting system : Promulgated by Decision No.1141-TC-CDKT data 1 November 1995 of the Ministry of finance.
Keywords: Accounting; Vietnam